(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Not only Plato and Aristotle are remembered in the communal Firenze. Epicurus also, mentioned by Dante, Boccaccio and Villani. But was there a Florentinian Epicureism? In their imaginary trip from the Commedia, Dante and Virgil –with divine help– manage to enter Ditis City, where the heretical are. In tombs full of fire, should be members of all sects and also the followers of Epicurus (died 270 BC), who was known through Cicero. In fact, the poet brings out notorious Ghibellines. Talks with Farinata degli Uberti and also intervenes with Guido Cavalcanti’s father, to whom gives an ambiguous answer, that is in my opinion, a ray of hope for one that is labeled as support the “Epicureans’ opinion”. Rather, he could be an averroist, which brings together a whole group of intellectuals of the time who deny the immortality of the soul.